Crescimento e sobrevivência de espécies arbóreas em plantio de enriquecimento de mata ciliar em restauração - Santos, Wander Laizo dos [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Studies have shown that the diversity of tropical forests undergoing restoration has not reached the expected values compared to the pre-existing native vegetation (reference ecosystems). Aiming at to increase de number of species in these forests, enrichment plantings have been recommended. The performance of seedlings of tree species planted under the canopy of forests under restoration, however, has not yet been tested experimentally. In this study, we aimed at comparatively evaluate growth and survival of nursery-raised seedlings of five native species of Tropical Semideciduous Forest, planted under the canopies of riparian forests being restored. We aimed also to elucidate the factors, besides the enrichment technique, influencing the performance of the species. We tested three different enrichment techniques (treatments) applied to five native tree species: Myroxylon peruiferum, Cedrela fissilis, Aspidosperma polyneuron, Astronium graveolens and Plinia rivularis, all non-pioneer species associated with late successional stages. We also analyzed the same species growing in the open, as a reference for what would be the development of species in conventional plantings. Enrichment treatments were: Girdling (planting in small clearings under mature trees which were deliberately killed by girdling and applying herbicide), Failure (planting in the lines, where the trees from the original planting were dead) and between lines of the original planting. For each individual planted in the open or enrichment, at the end of the dry season and at the end of the rainy season, during 27 months, we collected the following data: status (dead or alive), height, canopy diameter and stem diameter at the base. Based upon these data we calculated absolute increase in height, crown diameter and stem diameter, as well as mortality over time. For analysis of growth and survival, the entire period was considered ...

Estudos têm demonstrado que a diversidade das florestas em restauração está, geralmente, aquém dos ecossistemas de referência, ou seja, da vegetação nativa pré-existente. Entre as possíveis alternativas para aumento da diversidade dessas florestas têm sido propostos plantios de enriquecimento. Porém, o desempenho das mudas de espécies arbóreas plantadas sob florestas em restauração ainda não foi testado experimentalmente. O objetivo do presente estudo foi avaliar comparativamente o crescimento e a sobrevivência de cinco espécies arbóreas nativas da Floresta Estacional Semidecidual na condição de plantio de enriquecimento sob o dossel das matas ciliares em restauração, buscando elucidar os fatores que influenciam o desempenho das espécies. Testamos três diferentes técnicas de enriquecimento (tratamentos), aplicadas a cinco espécies arbóreas nativas: cabreúva - Myroxylon peruiferum, cedro - Cedrela fissilis, peroba rosa - Aspidosperma polyneuron, guaritá - Astronium graveolens e piúna - Plinia rivularis, todas espécies não-pioneiras associadas a estádios mais avançados da sucessão. Efetuamos também plantio das mesmas espécies a céu aberto, como referência de qual seria o desenvolvimento das espécies em um plantio convencional. Os tratamentos de enriquecimento foram: Anelamento (plantio em pequenas clareiras pela morte em pé de árvores adultas), Falha (plantio nas falhas do plantio original) e Entrelinhas (plantio nas entrelinhas do plantio original). Para cada indivíduo plantado, no enriquecimento ou a céu aberto, foram coletados, ao final da estação seca e ao final da estação chuvosa, durante 27 meses, dados de altura, diâmetro de copa, diâmetro do coleto e mortalidade ao longo do tempo. Com base nesses dados foram calculados os incrementos absolutos em altura, diâmetro de copa e diâmetro do coleto e mortalidade ao longo do período de ...
Growth and survival of tree species in enrichment planting of riparian forest restoration
Keywords: Arvores - Crescimento; Competição (Biologia); Florestas - Restauração; Ecologia das florestas tropicais; Recuperação ecológica; Trees Growth